The Effects of Using Steam to Preheat the Beds of an Adsorption Chiller with Desalination Function - Karol Sztekler; Wojciech Kalawa; Lukasz Mika; Lukasz Lis; Ewelina Radomska; Wojciech Nowak (Energies, 2021)
Adsorption chillers are a promising alternative to traditional compressor-based devices. Adsorption chillers can be supplied with low- or medium-temperature waste heat or heat from renewable energy sources. In addition, they can be used for water desalination purposes. Thus, the adsorption chillers are unique devices that meet essential problems of the modern world: a need to limit the negative impact of humankind on the natural environment and growing problems with access to drinking water. However, adsorption chillers also have disadvantages, including ineffective operation and large size. Therefore, in this paper, the influence of steam utilization on the operation of an adsorption chiller with water desalination function was investigated experimentally, which has not been done before. The research was carried out on the adsorption chiller, working on a silica gel–water pair, installed in the AGH UST Center of Energy. The chiller was modified to preheat the sorbent with the use of steam. The results show that the use of steam instead of water for preheating the bed leads to higher temperatures in the heat exchanger and the bed. As a result, heat transfer from the heating medium to the bed is more intense, and a significant shortening of the desorption process is observed. In the case of using steam for preheating, the desorption time was about 30 s, while for water, it was 300 s. Thanks to this solution, it is possible to reduce the size of the device and increase its efficiency. The proposed solution opens a new course of research on adsorption chillers and broadens the horizon of their applications, as steam is a by-product of many industrial processes.